Experiments and numerical simulations of nonlinear vibration responses of an assembly with friction joints – Application on a test structure named "Harmony". (March 2016) - Claeys, M.; Sinou, J-J.; Lambelin, J-P.; Todeschini, R.
Abstract: In presence of friction, the frequency response function of a metallic assembly is strongly dependent on the excitation level. The local stick-slip behavior at the friction interfaces induces energy dissipation and local stiffness softening. These phenomena are studied both experimentally and numerically on a test structure named "Harmony". Concerning the numerical part, a classical complete methodology from the finite element and friction modeling to the prediction of the nonlinear vibrational response is implemented. The well-known Harmonic Balance Method with a specific condensation process on the nonlinear frictional elements is achieved. Also, vibration experiments are performed to validate not only the finite element model of the test structure named "Harmony" at low excitation levels but also to investigate the nonlinear behavior of the system on several excitation levels. A scanning laser vibrometer is used to measure the nonlinear behavior and the local stick-slip movement near the contacts. Abstract : Highlights: Nonlinear vibration responses of an assembly with friction joints. Numerical simulation via reduced Harmonic Balance Method. Comparisons of experimental tests and numerical simulations for a mechanical industrial system.